PENGARUH SUPERVISI KEPALA SEKOLAH DAN INOVASI KURIKULUM TERINTEGRASI OLEH TENAGA KEPENDIDIKAN TERHADAP PROFESIONALISME GURU DAN PRESTASI BELAJAR SISWA DI MA AL UM PINANG RAYA KABUPATEN BENGKULU UTARA - Giyarsi Giyarsi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2020)
The purpose of this study  is to examine whether  there  is influence  of principal  supervision  and  innovation of in- tegrated  curriculum  development by educational staff on  teacher  professionalism and  student  achievement, either  direct  or indirect  influence.  This research  is a non  experimental quantitative research  using  data  analysis  method with path  analysis statistical test (path analysis). The results showed  two conclusions.  First there is the direct and indirect influence of the principal supervisory  variables  and  the innovative  variables  of integrated curriculum  development by the educational staff on teacher professionalism variables. The magnitude of this influence is the direct influence of principal supervision  on the professionalism of teachers  by 2.37%,  the direct influence of integrated curriculum development innovation on professionalism of teachers  by53.29%, indirect  influence  of principal  supervision  and  innovation of integrated curriculum  development on teacher  profes- sionalism  of 7 , 37%,  and  total influence  on teacher  professionalism equal  to 68,03%. Second, there  are direct and  indirect influence of principal supervision  variable,  innovation variable  of integrated curriculum development by educational staff, and teacher  professionalism variable  to learning achievement variable.  The amount of influence is the direct influence of principal supervision  on student  achievement of 1.32%,  with indirect effect of 13.26%. The direct effect of integrated curriculum devel- opment innovation on student  achievement is 1.41%,  with indirect effect of 62.85%. The direct influence  of teacher  profes- sionalism on student  achievement is 74.13%. And the total influence on student  achievement of the three variables is 77.52%. That is, partially, principal supervision  and  innovative  curriculum  development development by uneducated educational staff on student  achievement in MA Al Um Pinang  Raya, but simultaneously together  with the professionalism of teachers  give a big positive impact.